Review Article The Judiciary During the American War of Independence in 1776 - Maha Nadhim Azeez Al-Jawdah (Peerian Journals Publishing, 2025)
The American colonies were under British rule, and their judicial systems largely relied on British laws and the directives of the Crown. As tensions between the colonies and Britain escalated, questions began to arise regarding the legitimacy of British judicial authority and its suitability for the colonies’ growing needs and aspirations for independence.
Keywords: The Judiciary; the Federal Judiciary